Cost-effective Optimal Synthesis of the Efficiency Map of Permanent Magnet Synchronous Motors - Paolo Di Barba, Maria Evelina Mognaschi, Lidija Petkovska, Goga Cvetkovski (IOS Press, Amsterdam, 2022)
In the paper an original approach to efficiency map optimal synthesis is presented. A permanent magnet motor, working as controlled AC motor of synchronous type (PMSM), is selected as a case study. The first target of this research is to derive a lumped-parameter model of the motor (low-fidelity model), validated by magnetic field analysis (high-fidelity model). In turn, the end target is these two models application in a cost-effective optimisation procedures, where the goal is to identify the motor geometry maximizing the map area which is encompassed by a prescribed value for the motor efficiency.
Keywords: Permanent magnet synchronous motor (PMSM), efficiency map, shape optimisation, lumped-parameter model, magnetic field analysis